Cross-cultural and cross-linguistic perception of authentic emotions through speech: An acoustic–phonetic study with Brazilian and Swedish listeners - da Silva, Wellington; Barbosa, Plinio Almeida; Abelin, Åsa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
Swedish and Brazilian listeners were presented with authentic emotional speech samples of Brazilian Portuguese and Swedish. They judged on 5-point Likert scales the expression of basic emotions as described by eight adjectives in the utterances in Brazilian Portuguese and the expression of five emotional dimensions in the utterances in Swedish. The PCA technique revealed that two components explain more than 94% of the variance of the judges’ responses in both experiments. These components were predicted through multiple linear regressions from twelve acoustic parameters automatically computed from the utterances. The results point to a similar perception of the emotions between both cultures.